Impact of variation in practice in the prenatal reporting of variants of uncertain significance by commercial laboratories: Need for greater adherence to published guidelines. (18th September 2022) - Cornthwaite, Melissa; Turner, Kelly; Armstrong, Linlea; Boerkoel, Cornelius F.; Chang, Caitlin; Lehman, Anna; Nikkel, Sarah M.; Patel, Millan S.; Van Allen, Margot; Langlois, Sylvie
Abstract: Objective: To evaluate the impact of implementing commercial whole exome sequencing (WES) and targeted gene panel testing in pregnancies with fetal anomalies. Methods: A retrospective chart review of 124 patients with sequencing performed by commercial laboratories. Results: The diagnostic yield of WES and panel testing was 21.5% and 26%, respectively, based on likely pathogenic (LP) or pathogenic (P) variants. Forty‐two percent of exomes and 32% of panels analysed had one or more variants of uncertain significance (VUS) reported. A multidisciplinary in‐depth review of the fetal phenotype, disease phenotype, variant data, and, in some patients, additional prenatal or postnatal investigations increased the diagnostic yield by 5% for exome analysis and 6% for panel analysis. Conclusions: The diagnostic yield of WES and panel testing combined was 23% based on LP and P variants. Although the reporting of VUS contributed to a 5% increase in diagnostic yield for WES and 6% for panels, the large number of VUS reported by commercial laboratories has significant resource implications. Our results support the need for greater adherence to the recommendations on the prenatal reporting of VUS and the importance of a multidisciplinary approach that brings together clinical and laboratory expertise in prenatal genetics and genomics. Key points: What is already known about this topic? Prenatal exome sequencing in fetuses with structural anomalies identified on ultrasound increases the diagnostic yield by about 31%. What does this study add? This study demonstrates that the reporting of variants of uncertain significance (VUS) increases the diagnostic rate by 5%–6%. It illustrates the need for greater adherence to guidelines for the prenatal reporting of VUS as it varies greatly between laboratories. It emphasizes the importance of a multidisciplinary approach that brings together clinical and laboratory expertise in prenatal genetics and genomics.